Review of treatment modalities and clinical outcome of giant saccular posterior cerebral artery aneurysms - Andreas Theofanopoulos; Rajiv Kumar Khajuria; Dilaware Khan; Lucas Troude; Ben Waldau; Katharina Faust; Sajjad Muhammad (Brain and Spine)
Introduction: Giant saccular posterior cerebral artery (PCA) aneurysms are rare lesions carrying significant morbidity due to mass effect and present therapeutic challenges, mainly due to the challenging approach required for aneurysm obliteration. Research question: To review treatment modalities and outcomes of patients harboring giant (>2.5 cm) PCA saccular aneurysms distal to the basilar bifurcation. Materials and methods: A systematic literature review through PubMed and Scopus to identify cases of giant saccular PCA aneurysms treated either microsurgically or endovascularly. Patients’ demographics, aneurysm size, preoperative and postoperative neurologic status, clinical outcomes and follow-up information were retrieved. Results: Data from 33 studies including 55 patients were obtained. Mean patient age was 34.35 years. Mean maximum aneurysm diameter was 38.48 mm. Presentation was aneurysm rupture in 30.9 %, headache in 23.6 %, hemiparesis or tetraparesis in 12.7 %, hemianopsia in 10.9 % and hydrocephalus in 5.5 %. At least 30.9 % had significant brainstem compression. Treatment was endovascular in 23.6 %, microsurgical in 67.3 % and combined in 9.1 %. Debulking to reduce mass effect was required in 32.4 %. Preoperative mRS ranged from 1 to 5. A favorable outcome (mRS 0–2) was reported on 92.7 % of cases. Death rate was 3.6 %. The PCA was sacrificed in 40 % of the patients without severe neurologic morbidity. Follow-up ranged from 1 week to 11 years. Discussion and conclusion: Giant PCA aneurysms are amenable to both treatment modalities. PCA sacrifice may be required and is often well tolerated, presumably due to the rich collateral supply. Mass effect may necessitate debulking. PCA bypass may be required, but carries significant morbidity.